Expression of acetylcholine, its contribution to regulation of immune function and O2 sensing and phylogenetic interpretations of the African butterfly fish Pantodon buchholzi (Osteoglossiformes, Pantodontidae). Issue 111 (April 2021) - Capillo, Gioele; Zaccone, Giacomo; Cupello, Camila; Fernandes, Jorge Manuel Oliveira; Viswanath, Kiron; Kuciel, Michal; Zuwala, Krystyna; Guerrera, Maria Cristina; Aragona, Marialuisa; Icardo, Jose Manuel; Lauriano, Eugenia Rita
Abstract: Acetylcholine (Ach) is the main neurotransmitter in the neuronal cholinergic system and also works as a signaling molecule in non-neuronal cells and tissues. The diversity of signaling pathways mediated by Ach provides a basis for understanding the biology of the cholinergic epithelial cells and immune cells in the gill of the species studied. NECs in the gill were not found surprisingly, but specialized cells showing the morphological, histochemical and ultrastructural characteristics of eosinophils were located in the gill filaments and respiratory lamellae. Much remains unknown about the interaction between the nerves and eosinophils that modulate both the release of acetylcholine and its nicotinic and muscarinic receptors including the role of acetylcholine in the mechanisms of O2 chemosensing. In this study we report for the first time the expression of Ach in the pavement cells of the gill lamellae in fish, the mast cells associated with eosinophils and nerve interaction for both immune cell types, in the gill of the extant butterfly fish Pantodon buchholzi . Multiple roles have been hypothesized for Ach and alpha nAChR in the gills. Among these there are the possible involvement of the pavement cells of the gill lamellae as O2 chemosensitive cells, the interaction of Ach positive mast cells with eosinophils and interaction of eosinophils with nerve terminals. This could be related to the use of the vesicular acetylcholine transporter (VAChT) and the alpha 2 subunit of the acetylcholine nicotinic receptor (alpha 2 nAChR). These data demonstrate the presence of Ach multiple sites of neuronal and non-neuronal release and reception within the gill and its ancestral signaling that arose during the evolutionary history of this conservative fish species. Highlights: Immunocytochemical markers of acetylcholine and nAChR in the gill of butterfly fish. Eosinophils and mast cells and their nerve interaction. Absence of NECs is compensated by the cholinergic epithelial cells. Ach signaling during evolutionary history.